Development of molecular diagnostic test to quantify Rhizobium leguminosarum bv. viciae (rhizobia group E/F) in soil - Stephen Barnett; Ross A. Ballard; Danièle Giblot-Ducray; Kelly Hill; Alan McKay; Herdina; Elizabeth A. Farquharson (Plant and Soil, 2026)
Aims Rhizobia are essential for nitrogen fixation in legumes. The current method for enumerating rhizobia in soil by the Most Probable Number (MPN) method is costly and time consuming. This paper describes the development of a qPCR test to quantify Rhizobium leguminosarum bv. viciae (Rlv) in soil. Methods TaqMan probe and primers were developed . Specificity of qPCR was confirmed against Rlv and non-target rhizobia and compared to vetch nodulation. Relationship between qPCR results and Rlv numbers was assessed by comparing qPCR of Rlv strains added into sand at known cell density to plate counts on agar. The reliability of the test was assessed on 41 field soils and compared to quantification by MPN on vetch and symbiotic performance of rhizobia in soil extracts was examined on field pea and faba bean. Results The developed test was specific for Rlv, with 42 strains testing positive for both qPCR and nodulation of vetch and 42 other rhizobia negative for both qPCR and nodulation. A dilution series of two Rlv strains inoculated into sand produced a tight correlation (R 2 = 0.92) between qPCR data and plate counts. Assessment of field soils indicated a significant relationship ( P < 0.001, R 2 = 0.85) between qPCR and MPN and between qPCR and nitrogen fixation capacity with field pea (R 2 = 0.82) and faba bean (R 2 = 0.51). Conclusion The qPCR test developed is specific for Rlv strains and shows high correlation with plate counts, MPN population estimates and symbiotic performance. This test is now delivered as a commercial service to growers and researchers as “PREDICTA® rNod”.

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Revised PVT equations of state for almandine and spessartine garnets: implications for piezobarometry - Ross J. Angel; Marta Morana; Sergio Speziale; Nicola P. M. Casati; Alan B. Woodland; Matteo Alvaro; Guy L. Hovis; Mario Tribaudino (Contributions to Mineralogy and Petrology, 2026)

Inshore and offshore marine migration pathways of Atlantic salmon post‐smolts from multiple rivers in Scotland, England, Northern Ireland, and Ireland - Jessica R. Rodger; Jessie Lilly; Hannele M. Honkanen; Diego del Villar; Richard Kennedy; Niall Ó. Maoiléidigh; Patrick Boylan; Robert Rosell; David J. Morris; Ross O'Neill; Catherine Waters; Deirdre Cotter; et al. (Journal of Fish Biology, 2025)
The migratory behavior of Atlantic salmon ( Salmo salar ) post‐smolts in coastal waters is poorly understood. In this collaborative study, 1914 smolts, from 25 rivers, in four countries were tagged with acoustic transmitters during a single seasonal migration. In total, 1105 post‐smolts entered the marine study areas and 438 (39.6%) were detected on a network of 414 marine acoustic receivers and an autonomous underwater vehicle. Migration pathways (defined as the shortest distance between two detections) of up to 575 km and over 100 days at sea were described for all 25 populations. Post‐smolts from different rivers, as well as individuals from the same river, used different pathways in coastal waters. Although difficult to generalize to all rivers, at least during the year of this study, no tagged post‐smolts from rivers draining into the Irish Sea were detected entering the areas of sea between the Hebrides and mainland Scotland, which is associated with a high density of finfish aquaculture. An important outcome of this study is that a high proportion of post‐smolts crossed through multiple legislative jurisdictions and boundaries during their migration. This study provides the basis for spatially explicit assessment of the impact risk of coastal pressures on salmon during their first migration to sea.

Extreme Drought Increases the Temporal Variability of Grassland Productivity by Suppressing Dominant Grasses - Wentao Luo; Naohiro I. Ishii; Taofeek O. Muraina; Lin Song; Niwu Te; Robert J. Griffin‐Nolan; Ingrid J. Slette; Samuel R. P. J. Ross; Takehiro Sasaki; Jennifer A. Rudgers; Melinda D. Smith; Alan K. Knapp; et al. (Ecology Letters, 2025)
Extreme droughts are intensifying, yet their impact on temporal variability of grassland functioning and its drivers remains poorly understood. We imposed a 6‐year extreme drought in two semiarid grasslands to explore how drought influences the temporal variability of ANPP and identify potential stabilising mechanisms. Drought decreased ANPP while increasing its temporal variability across grasslands. In the absence of drought, ANPP variability was strongly driven by the dominant plant species (i.e., mass‐ratio effects), as captured by community‐weighted traits and species stability. However, drought decreased the dominance of perennial grasses, providing opportunities for subordinate species to alter the stability of productivity through compensatory dynamics. Specifically, under drought, species asynchrony emerged as a more important correlate of ANPP variability than community‐weighted traits or species stability. Our findings suggest that in grasslands, prolonged, extreme droughts may decrease the relative contribution of mass‐ratio effects versus compensatory dynamics to productivity stability by reducing the influence of dominant species.

A framework for reconstructing marine heatwaves from individual foraminifera in sedimentary archives - Casey Saenger; Carlos Jimenez-Diaz; Alexander Gagnon; Alan Mix; Andrew Ross; Tongtong Xu (Frontiers in Marine Science, 2024)
Marine heatwaves (MHWs) are warm sea surface temperature (SST) anomalies with substantial ecological and economic consequences. Observations of MHWs are based on relatively short instrumental records, which limit the ability to forecast these events on decadal and longer timescales. Paleoclimate reconstructions can extend the observational record and help to evaluate model performance under near future conditions, but paleo-MHW reconstructions have received little attention, primarily because marine sediments lack the temporal resolution to record short-lived events. Individual foraminifera analysis (IFA) of paleotemperature proxies presents an intriguing opportunity to reconstruct past MHW variability if strong relationships exist between SST distributions and MHW metrics. Here, we describe a method to test this idea by systematically evaluating relationships between MHW metrics and SST distributions that mimic IFA data using a 2000-member linear inverse model (LIM) ensemble. Our approach is adaptable and allows users to define MHWs based on multiple duration and intensity thresholds and to model seasonal biases in five different foraminifera species. It also allows uncertainty in MHW reconstructions to be calculated for a given number of IFA measurements. An example application of our method at 12 north Pacific locations suggests that the cumulative intensity of short-duration, low-intensity MHWs is the strongest target for reconstruction, but that the error on reconstructions will rely heavily on sedimentation rate and the number of foraminifera analyzed. This is evident when a robust transfer function is applied to new core-top oxygen isotope data from 37 individual Globigerina bulloides at a site with typical marine sedimentation rates. In this example application, paleo-MHW reconstructions have large uncertainties that hamper comparisons to observational data. However, additional tests demonstrate that our approach has considerable potential to reconstruct past MHW variability at high sedimentation rate sites where hundreds of foraminifera can be analyzed.

Tagging of Atlantic bluefin tuna off Ireland reveals use of distinct oceanographic hotspots - Camille M.L.S. Pagniello; Niall Ó Maoiléidigh; Hugo Maxwell; Michael R. Castleton; Emilius A. Aalto; Jonathan J. Dale; Robert J. Schallert; Michael J.W. Stokesbury; Ronán Cosgrove; Simon Dedman; Alan Drumm; Ross O'Neill; et al. (Progress in Oceanography, 2023)

Lions and brown bears colonized North America in multiple synchronous waves of dispersal across the Bering Land Bridge - Alexander T. Salis; Sarah C. E. Bray; Michael S. Y. Lee; Holly Heiniger; Ross Barnett; James A. Burns; Vladimir Doronichev; Daryl Fedje; Liubov Golovanova; C. Richard Harington; Bryan Hockett; Pavel Kosintsev; et al. (Molecular Ecology, 2022)
The Bering Land Bridge connecting North America and Eurasia was periodically exposed and inundated by oscillating sea levels during the Pleistocene glacial cycles. This land connection allowed the intermittent dispersal of animals, including humans, between Western Beringia (far northeast Asia) and Eastern Beringia (northwest North America), changing the faunal community composition of both continents. The Pleistocene glacial cycles also had profound impacts on temperature, precipitation and vegetation, impacting faunal community structure and demography. While these palaeoenvironmental impacts have been studied in many large herbivores from Beringia (e.g., bison, mammoths, horses), the Pleistocene population dynamics of the diverse guild of carnivorans present in the region are less well understood, due to their lower abundances. In this study, we analyse mitochondrial genome data from ancient brown bears ( Ursus arctos ; n = 103) and lions ( Panthera spp.; n = 39), two megafaunal carnivorans that dispersed into North America during the Pleistocene. Our results reveal striking synchronicity in the population dynamics of Beringian lions and brown bears, with multiple waves of dispersal across the Bering Land Bridge coinciding with glacial periods of low sea levels, as well as synchronous local extinctions in Eastern Beringia during Marine Isotope Stage 3. The evolutionary histories of these two taxa underline the crucial biogeographical role of the Bering Land Bridge in the distribution, turnover and maintenance of megafaunal populations in North America.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Joint effects of climate, tree size, and year on annual tree growth derived from tree‐ring records of ten globally distributed forests - Kristina J. Anderson‐Teixeira; Valentine Herrmann; Christine R. Rollinson; Bianca Gonzalez; Erika B. Gonzalez‐Akre; Neil Pederson; M. Ross Alexander; Craig D. Allen; Raquel Alfaro‐Sánchez; Tala Awada; Jennifer L. Baltzer; Patrick J. Baker; et al. (Global Change Biology, 2022)
Tree rings provide an invaluable long‐term record for understanding how climate and other drivers shape tree growth and forest productivity. However, conventional tree‐ring analysis methods were not designed to simultaneously test effects of climate, tree size, and other drivers on individual growth. This has limited the potential to test ecologically relevant hypotheses on tree growth sensitivity to environmental drivers and their interactions with tree size. Here, we develop and apply a new method to simultaneously model nonlinear effects of primary climate drivers, reconstructed tree diameter at breast height (DBH), and calendar year in generalized least squares models that account for the temporal autocorrelation inherent to each individual tree's growth. We analyze data from 3811 trees representing 40 species at 10 globally distributed sites, showing that precipitation, temperature, DBH, and calendar year have additively, and often interactively, influenced annual growth over the past 120 years. Growth responses were predominantly positive to precipitation (usually over ≥3‐month seasonal windows) and negative to temperature (usually maximum temperature, over ≤3‐month seasonal windows), with concave‐down responses in 63% of relationships. Climate sensitivity commonly varied with DBH (45% of cases tested), with larger trees usually more sensitive. Trends in ring width at small DBH were linked to the light environment under which trees established, but basal area or biomass increments consistently reached maxima at intermediate DBH. Accounting for climate and DBH, growth rate declined over time for 92% of species in secondary or disturbed stands, whereas growth trends were mixed in older forests. These trends were largely attributable to stand dynamics as cohorts and stands age, which remain challenging to disentangle from global change drivers. By providing a parsimonious approach for characterizing multiple interacting drivers of tree growth, our method reveals a more complete picture of the factors influencing growth than has previously been possible.

Comparative genomics of Cp8viruses with special reference to Campylobacter phage vB_CjeM_los1, isolated from a slaughterhouse in Ireland - Lisa O’Sullivan; Alan Lucid; Horst Neve; Charles M. A. P. Franz; Declan Bolton; Olivia McAuliffe; R. Paul Ross; Aidan Coffey (Archives of Virology, 2018)

A qualitative investigation among men who have sex with men on the acceptability of performing a self- or partner anal exam to screen for anal cancer - Seyram A. Butame; Sylvia Lawler; Joseph T. Hicks; J. Michael Wilkerson; Lu-Yu Hwang; Sarah Baraniuk; Michael W. Ross; Elizabeth Yu Chiao; Alan G. Nyitray (Cancer Causes & Control, 2017)

Continuous in situ monitoring of sediment deposition in shallow benthic environments - James Whinney; Ross Jones; Alan Duckworth; Peter Ridd (Coral Reefs, 2017)

Species‐specific responses to climate change and community composition determine future calcification rates of Florida Keys reefs - Remy R. Okazaki; Erica K. Towle; Ruben van Hooidonk; Carolina Mor; Rivah N. Winter; Alan M. Piggot; Ross Cunning; Andrew C. Baker; James S. Klaus; Peter K. Swart; Chris Langdon (Global Change Biology, 2017)
Anthropogenic climate change compromises reef growth as a result of increasing temperatures and ocean acidification. Scleractinian corals vary in their sensitivity to these variables, suggesting species composition will influence how reef communities respond to future climate change. Because data are lacking for many species, most studies that model future reef growth rely on uniform scleractinian calcification sensitivities to temperature and ocean acidification. To address this knowledge gap, calcification of twelve common and understudied Caribbean coral species was measured for two months under crossed temperatures (27, 30.3 °C) and CO 2 partial pressures ( p CO 2 ) (400, 900, 1300 μatm). Mixed‐effects models of calcification for each species were then used to project community‐level scleractinian calcification using Florida Keys reef composition data and IPCC AR 5 ensemble climate model data. Three of the four most abundant species, Orbicella faveolata, Montastraea cavernosa, and Porites astreoides , had negative calcification responses to both elevated temperature and p CO 2 . In the business‐as‐usual CO 2 emissions scenario, reefs with high abundances of these species had projected end‐of‐century declines in scleractinian calcification of >50% relative to present‐day rates. Siderastrea siderea , the other most common species, was insensitive to both temperature and p CO 2 within the levels tested here. Reefs dominated by this species had the most stable end‐of‐century growth. Under more optimistic scenarios of reduced CO 2 emissions, calcification rates throughout the Florida Keys declined S. siderea are not already dominant. This study demonstrates how species composition influences reef community responses to climate change and how reduced CO 2 emissions can limit future declines in reef calcification.

Global impacts of the 1980s regime shift - Philip C. Reid; Renata E. Hari; Grégory Beaugrand; David M. Livingstone; Christoph Marty; Dietmar Straile; Jonathan Barichivich; Eric Goberville; Rita Adrian; Yasuyuki Aono; Ross Brown; James Foster; et al. (Global Change Biology, 2016)
Despite evidence from a number of Earth systems that abrupt temporal changes known as regime shifts are important, their nature, scale and mechanisms remain poorly documented and understood. Applying principal component analysis, change‐point analysis and a sequential t ‐test analysis of regime shifts to 72 time series, we confirm that the 1980s regime shift represented a major change in the Earth's biophysical systems from the upper atmosphere to the depths of the ocean and from the Arctic to the Antarctic, and occurred at slightly different times around the world. Using historical climate model simulations from the Coupled Model Intercomparison Project Phase 5 ( CMIP 5) and statistical modelling of historical temperatures, we then demonstrate that this event was triggered by rapid global warming from anthropogenic plus natural forcing, the latter associated with the recovery from the El Chichón volcanic eruption. The shift in temperature that occurred at this time is hypothesized as the main forcing for a cascade of abrupt environmental changes. Within the context of the last century or more, the 1980s event was unique in terms of its global scope and scale; our observed consequences imply that if unavoidable natural events such as major volcanic eruptions interact with anthropogenic warming unforeseen multiplier effects may occur.

Plant Conservation Challenges in the Bahama Archipelago - Eric Carey; Lynn Gape; B. Naqqi Manco; Dion Hepburn; Ross L. Smith; Lindy Knowles; David Knowles; Mark Daniels; Michael A. Vincent; Ethan Freid; Brett Jestrow; M. Patrick Griffith; et al. (The Botanical Review, 2014)

Early warning signals: the charted and uncharted territories - Carl Boettiger; Noam Ross; Alan Hastings (Theoretical Ecology, 2013)

Assessment of transcriptomal analysis of varicella-zoster-virus gene expression in patients with and without post-herpetic neuralgia - G. H. Ashrafi; Esther Grinfeld; Paul Montague; Thorsten Forster; Alan Ross; Peter Ghazal; Fiona Scott; Judith Breuer; Roslyn Goodwin; Peter G. E. Kennedy (Virus Genes, 2010)

Molecular sexing of African rhinoceros - Lindsay Peppin; Ross McEwing; Rob Ogden; Robert Hermes; Cindy Harper; Alan Guthrie; Gary R. Carvalho (Conservation Genetics, 2010)

Isolation and Analysis of Bacteria with Antimicrobial Activities from the Marine Sponge Haliclona simulans Collected from Irish Waters - Jonathan Kennedy; Paul Baker; Clare Piper; Paul D. Cotter; Marcella Walsh; Marlies J. Mooij; Marie B. Bourke; Mary C. Rea; Paula M. O’Connor; R. Paul Ross; Colin Hill; Fergal O’Gara; et al. (Marine Biotechnology, 2009)

Phylogeography of lions ( Panthera leo ssp.) reveals three distinct taxa and a late Pleistocene reduction in genetic diversity - ROSS BARNETT; BETH SHAPIRO; IAN BARNES; SIMON Y. W. HO; JOACHIM BURGER; NOBUYUKI YAMAGUCHI; THOMAS F. G. HIGHAM; H. TODD WHEELER; WILFRIED ROSENDAHL; ANDREI V. SHER; MARINA SOTNIKOVA; TATIANA KUZNETSOVA; et al. (Molecular Ecology, 2009)
Lions were the most widespread carnivores in the late Pleistocene, ranging from southern Africa to the southern USA, but little is known about the evolutionary relationships among these Pleistocene populations or the dynamics that led to their extinction. Using ancient DNA techniques, we obtained mitochondrial sequences from 52 individuals sampled across the present and former range of lions. Phylogenetic analysis revealed three distinct clusters: (i) modern lions, Panthera leo ; (ii) extinct Pleistocene cave lions, which formed a homogeneous population extending from Europe across Beringia (Siberia, Alaska and western Canada); and (iii) extinct American lions, which formed a separate population south of the Pleistocene ice sheets. The American lion appears to have become genetically isolated around 340 000 years ago, despite the apparent lack of significant barriers to gene flow with Beringian populations through much of the late Pleistocene. We found potential evidence of a severe population bottleneck in the cave lion during the previous interstadial, sometime after 48 000 years, adding to evidence from bison, mammoths, horses and brown bears that megafaunal populations underwent major genetic alterations throughout the last interstadial, potentially presaging the processes involved in the subsequent end‐Pleistocene mass extinctions.

Genome-wide reduction in transcriptomal profiles of varicella-zoster virus vaccine strains compared with Parental Oka strain using long oligonucleotide microarrays - Esther Grinfeld; Alan Ross; Thorsten Forster; Peter Ghazal; Peter G. E. Kennedy (Virus Genes, 2009)

Lost populations and preserving genetic diversity in the lion Panthera leo: Implications for its ex situ conservation - Ross Barnett; Nobuyuki Yamaguchi; Ian Barnes; Alan Cooper (Conservation Genetics, 2006)

Land‐use impacts and water quality targets in the intensive dairying catchment of the Toenepi Stream, New Zealand - Robert J. Wilcock; Ross M. Monaghan; John M. Quinn; Alan M. Campbell; Bruce S. Thorrold; Maurice J. Duncan; Alec W. McGowan; Keith Betteridge (New Zealand Journal of Marine and Freshwater Research, 2006)
Water quality monitoring in Toenepi Stream, New Zealand, started in 1995 in a study of dairy farming influences on lowland stream quality and has continued since then with brief interruptions. Surveys have provided information about changes in farm and soil management practices as they relate to environmental sustainability. Although average water quality in Toenepi Stream has changed little during 1995–2004, there have been some notable improvements. Water clarity measured by black disc has improved from 0.6m to 1.5m, and median ammonia‐N and nitrate‐N concentrations have declined by 70% and 57%, respectively. The frequency and magnitude of extreme concentrations have declined—most notably for nitrogen (N) forms, which also had decreased mean values. Specific yields for suspended solids (SS) and phosphorus (P) forms in 2002–04 were 47–67% of 1995–97 values, mainly because of lower water yields. Reduced specific yields for N forms in 2002–04 (34–37% of 1995–97 yields) were also attributable to lower mean concentrations in stream water. Faecal bacteria concentrations have not abated and are on average 2–3 times recommended guideline values for contact recreation. Fewer dairy farms and an increased proportion irrigating dairyshed effluent to land, rather than discharging it to the stream via two‐pond systems, were likely causes of improvement in water quality. Water quality targets were developed for Toenepi Stream to achieve contact recreation criteria for the Piako River (downstream) and for intrinsic habitat values for Toenepi Stream. A range of mitigation measures has been formulated to meet these targets, but substantial uptake of sustainable farming practices is needed to improve water quality in Toenepi Stream.

Effectiveness of a Coral-Derived Surfacing Material for Reducing Sediment Production on Unpaved Roads, Schoffield Barracks, Oahu, Hawaii - Alan D. Ziegler; Ross A. Sutherland (Environmental Management, 2006)

A QTL affecting daily feed intake maps to Chromosome 2 in pigs - Ross D. Houston; Chris S. Haley; Alan L. Archibald; Kellie A. Rance (Mammalian Genome, 2005)

How deep was the Dudley (UK) earthquake of 22 September 2002? - Ross Heyburn; David Bowers; Neil Selby; Alan Douglas (Journal of Seismology, 2005)

The importance of alcohol-induced muscle disease - Victor R. Preedy; Kay Ohlendieck; Junko Adachi; Michael Koll; Alan Sneddon; Ross Hunter; Rajkumar Rajendram; David Mantle; Timothy J. Peters (Journal of Muscle Research and Cell Motility, 2003)

NEPTUNE: Real-Time Ocean and Earth Sciences at the Scale of a Tectonic Plate - John Delaney; Ross Heath; Bruce Howe; Alan Chave; Harold Kirkham (Oceanography, 2000)

Sediment entrainment in karst basins - Jordi Colomer; John Alan Ross; Xavier Casamitjana (Aquatic Sciences, 1998)